Digital or Sad Poetry: The Enthusiasm over Sadness on Wattpad - Mauludi, Anugrah Bulan; Afdholy, Nadya; Setijowati, Adi (Wanastra: Jurnal Bahasa dan Sastra, 2025)
Despite of indicating the development of literature in a modern world, Wattpad allows any type of influence to enter its platform. Whereas there are many people who are under the age of adult, but they are writing poems that are popular. Wattpad’s poetry itself has many themes related to sadness. The aim of this research is to study about enthusiasm over sadness in Wattpad’s poetry. The method was based on qualitative-quantitative mixed method. It is found that the images of sadness revolve around guilt, depression, loneliness, trauma, and betrayal. Based on the qualitative approach, findings show that depression’s theme is portrayed more than the rest. This article proposes to conduct study of Wattpad literature based on popular works, also to use a qualitative approach to investigate the content of the platform itself. The neutrality of Wattpad’s comments is considered non-canonical from a quantitative sentiment analysis point of view and therefore requires greater attention for future research.